INTEGRATING DIGITAL ELEVATION MODEL, LANDUSE/LANDCOVER AND FLOOD FREQUENCY ANALYSIS: A DETERMINISTIC APPROACH TO FLOOD INUNDATION AND RISK MODELING OF MAKURDI ALONG ITS RIVER BENUE REACH (FUDMA JOURNAL OF SCIENCES, 2021)
The study applied GIS techniques to integrate Digital Elevation Model (DEM), Landuse/Landcover (LULC) and flood frequency analyses to determine extent of flood hazard inundation of Makurdi town along its River Benue reach following extreme discharges and stage levels. Annual maximum stage and discharge data from 1914 to 2015 was analyzed using Gumbelâ€™s distribution to predict flood flow for different return periods (T): 5, 10, 25, 50, 75, and 100. A goodness of fit test was conducted using Chi square statistics, which was insignificant indicating that River Benue at Makurdi flood flow fits the Gumbel distribution. Combining this result with DEM and classified LULC data, the GIS spatial analyst tool was used to estimate the areal extent of landuse that will be inundated per return period. The result shows extent of flood inundation based on current landuse pattern for the respective return periods of predicted extreme stage / discharge likely due to climate change to be as follows: bareland (1.69, 1.74, 1.78, 1.84, 1.83, 1.89 km2); settlement/built-up (5.38, 5.50, 5.63, 5.76, 5.76, 6.02 km2); farmlands (272.27, 283.59, 295.10, 306.43, 306.43,and 317.49 km2); Vegetation (91.56, 95.26, 98.78, 102.45, 102.48, and 105.95 km2); water bodies (0.21,0.21, 0.22,0.22,0.22, and 0.22 km2) and Wetlands (44.14,  45.80, 47.48, 30.36,49.42 and 50.78 km2). This reveals a general increase in the extent of flood inundation at progressive recurrence interval, and predicted rising extreme river stage heights / discharge except for the flood with 50 year recurrence interval. The study recommends that NEMA and Benue State Urban Development Board
Keywords: Deterministic, River, Flood, frequency, Inundation, Modeling